Reliability-based optimization model for operation and maintenance strategy of subsea injection pumps in offshore natural gas facility - Altarejos, Marco Antonio O.
This study aimed to assess the energy benefits generated of risk-based approach operation and maintenance strategy using probabilistic and optimization models to improve the reliability of subsea injection pump system in offshore natural gas facility. The study modeled the failure of the methanol subsea injection pumps, considered to be one of the most critical process equipment, using Weibull distribution. The probabilistic model is then used as an input in an optimization model that maximizes the running or operation time of the pump system. A prioritization tool was used in assessing the risk factors, which were then used by another optimization model to determine the maintenance strategy. Substantial benefits can be definitely obtained by enhancing the reliability of the critical equipment through application of the technique in the study. These benefits can then be used as a basis in establishing the operation and Maintenance policies in vital energy facilities.